Study on high-CO2 tolerant Dunaliella salina and its mechanism via transcriptomic analysis - Huang, Bo; Qu, Gaopin; He, Yulong; Zhang, Jinli; Fan, Jianhua; Tang, Tao (Frontiers in Bioengineering and Biotechnology, 2022)
Microalgae has been regarded as a promising method for reducing CO2 emission. High CO2 concentration generally inhibits algal growth, and previous studies have mostly focused on breeding freshwater algae with high CO2 tolerance. In this study, one marine algal strain Dunaliella salina was grown under 0.03%-30 % CO2 and 3% NaCl conditions, and was evaluated to determine its potential for CO2 assimilation. The results showed that Dunaliella salina could tolerate 30% CO2, and its maximum biomass concentration could reach 1.13 g·L-1 after 8 day incubation, which was 1.85 times higher than that of incubation in air (0.03%). The phenomenon of high-CO2 tolerance in Dunaliella salina culture was discussed basing on transcriptome analysis. The results showed that Dunaliella salina was subjected to oxidative stress under 30% CO2 conditions, and the majority genes involving in antioxidant system, such as SOD, CAT and APX genes were upregulated to scavenge ROS. In addition, most of the key enzyme genes related to photosynthesis, carbon fixation and metabolism were up-regulated, which are consistent with the higher physiological and biochemical values for Dunaliella salina incubation under 30% CO2.